Implementation of Cooperative Learning Model to Improve Students' Learning Outcomes on the Material of Knowing Allah Through Asmaul Husana at SD Negeri 096747 Padang Mainu - Nurhayati, Siti; Suyanti; Ramadhani, Riyo; Manurung, Eliana Saprida; Iziati (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2024)
This study aims to examine the application of cooperative learning models in an effort to improve student learning outcomes on the material "Getting to Know Allah Through Asmaul Husna" in class II SDN 096747 Padang Mainu in the 2024/2025 academic year. Cooperative learning was chosen because it has the potential to increase interaction between students, strengthen understanding of the material, and encourage cooperation in groups. The method used is classroom action research (CAR) which is carried out in two cycles. Each cycle consists of planning, implementation, observation, and reflection. Data were collected through observation, interviews, and learning outcome tests. The results of the study showed that the application of cooperative learning models can improve student learning outcomes, both in terms of knowledge and attitudes, and create a more active and enjoyable learning atmosphere. Thus, it can be concluded that the use of cooperative learning models is effective in improving learning outcomes on the material "Getting to Know Allah Through Asmaul Husna" in class II SDN 096747 Padang Mainu